Workshop: Strategi Efektif Dalam Penanganan Cedera Atlet Untuk Meningkatkan Kualitas Menuju Prestasi Maksimal - Siregar, Abdul Hakim; Zulaini, Zulaini; Siregar, Nurhamida Sari; Sembiring, Masta Marselina (IHSAN : JURNAL PENGABDIAN MASYARAKAT, 2024)
The aim of the community-based PKM entitled "Workshop: Effective Strategies for Handling Athlete Injuries to Improve Quality for Maximum Performance" is to provide a comprehensive understanding of the various types of injuries often experienced by athletes, such as muscle, ligament, joint and bone injuries. The partners' targets are North Sumatra Indonesian Cricket Association Provincial Management. The activity subject consists of 33 members. The activity will be carried out on 6-8 August 2024. Location of the 469th Corps Pasgat Battalion, North Sumatra Province, stages of partner assistance and empowerment, stages of partner participation in program implementation and evaluation of partner participation in program implementation. The results of the activities show an increase in participants' knowledge and skills in dealing with athlete injuries more precisely and measurably. Participants succeeded in understanding the types of injuries commonly experienced by athletes and are able to provide fast and effective first aid, which is expected to minimize the long-term impact of the injury. In addition, participants also master comprehensive and structured rehabilitation strategies, enabling them to better assist the athlete's recovery process. This workshop was also successful in increasing awareness of the importance of injury prevention, where participants were able to apply safe exercise techniques to reduce the risk of injury in the future. During the recovery period, participants understand how to modify the training program to remain optimal without worsening the injury. As the end result, workshop participants were able to design effective strategies to restore athlete performance to peak, so that athlete performance can continue to improve.